Morphological and molecular characterization of Lenonchium zanjanense sp. n. (Dorylaimida, Nordiidae) from Iran, with new insights into the phylogeny of the genus and a revision of its taxonomy. (2020) - Asgari, M.; Eskandari, A.; Karani, H.M.; Abolafia, J.; Peña-Santiago, R.
Abstract: The new species Lenonchium zanjanense sp. n. is described from a natural habitat of Zanjan province, Iran, including line, light microscopy and scanning electron microscopy illustrations and a molecular (18S, 28S) study. It is characterized by its 3.50–4.51 mm long body, rounded lip region, continuous and 13.5–15.5 µm broad, odontostyle 21–24 µm long, neck 362–490 µm long, double guiding ring, pharyngeal expansion 190–285 µm long, female genital system didelphic–amphidelphic, uterus simple and 185–320 µm long or 3.4–5.9 times the corresponding body diameter, vulva nearly equatorial ( V = 45–53), tail conical-elongated to filiform (90–165 µm, c = 23–43, c ′ = 2.4–5.3) with three or four mucro-like projections at the tip, spicules 58–64 µm long and 16–21 contiguous ventromedian supplements ending at the level of the anterior end of the spicules. The taxonomy of the genus is updated, with an emended diagnosis, list of species, key to their identification and a compendium of their main morphometrics. Lenonchium asterocaudatum is regarded as identical and a junior synonym of L. denticaudatum. New insights into the phylogeny of the group are also provided, and the classification of Lenonchium within Nordiidae is seriously questioned.